Was the Collectivization Really Neccesary? Recent Contributions to a Long Debate - Saborido, Jorge (Revista de Historia Social y de las Mentalidades, 2024)
This paper proposes the revision of the last contributions to the long debate linked with the collectivization of the soviet agriculture ordered by stalin in 1929. Beyond the appalling social consequences, also object of historiographical debates, we discussed if his objective, the creation of collective farms destined to the modernization of the country, effectively fulfilled that function.
Keywords: Stalinism; Collectivization; Collective Farms; Modernization